CPC-128 Start Smart Then Focus – a Survey of Antimicrobial Stewardship Guidelines Implementation in England. (12th March 2013) - Howard, P; Cooke, J; Fry, C; McNulty, C; Khoda, H; Wellstead, S; Stockley, J; Loveday, H; Brown, L
Abstract : Background: Start Smart then Focus Antimicrobial Stewardship (AMS) guidance for England was launched in November 2011 on European Antimicrobial Awareness Day. Purpose: To identify the extent of guideline implementation, whether the guidelines had improved AMS, and to collect examples of good practise. Materials and Methods: A web-based survey was developed using SurveyMonkey software, piloted, and then distributed through the microbiology, infectious diseases and pharmacy networks in July 2012. Results: There were 74 responses (44%) to the Start Smart then Focus (SSTF) guidance by September. SSTF was rated excellent or good by 65% for making AMS a Trust priority; by 57% for improving their AMS infrastructure; by 51% for improving prescribing practise; by 57% for improving audit and by 31% for improved usage reporting. Only 12% to 22% thought it was poor or less than satisfactory for the same criteria. A formal review of SSTF has been done by 41%, with 17% planning to do so. 86% had done an informal review. 52% had developed an action plan. The main barriers to implementation were a lack of microbiology/infectious diseases time, then pharmacist time. An established AMS group, an enthusiastic pharmacist or microbiologist, or adequate time, were the main facilitators. Putting the indication and duration or a review date on in-patient antimicrobial prescriptions were in place prior to SSTF in 67% and 73% of centres respectively. Since SSTF a further 9% have started and another 13% and 10% plan to implement these suggestions by April 2013. Additional antimicrobial ward rounds have started or are planned since SSTF in medical wards by 20%, surgical wards by 19% and paediatrics by 10% of centres. Conclusions: The Start Smart then Focus Antimicrobial Stewardship guidance has helped to further implement AMS in England. No conflict of interest.